FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN CALON MAHASISWA MEMILIH FAKULTAS EKONOMI UNIVERSITAS PEKALONGAN - M. Shofiyuddin (Fakultas Ekonomi Universitas Pekalongan, 2017)
This research to know and analize how to influence to strategic location, the affordable costs, infrastructure, interesting building, lectures qualification magister, unaffected friends to decision of candidate studies of students chooseFacultyof Economic University of Pekalongan either simultane ously or partially, and what is the factor who the most influencial.The data used are primary data collected throught survey method using questionary and tasted for Validity and Reliability, and tested clasification classic assumption,the sample was obtained using random sampling method and then analyzed using multiple regression techniques to test the hypothesis.The result of this studi indicate there is significant influence strategic location, the affordable costs. Infrastructure, interesingt building, lectures qualification magister infrastrucsture,unaffected friend choose economy fakulty University of Pekalongan theirs simultane ously, while partiallythere is one factor not significant influenceunaffected frieds.The factor who the most in influential is strategic location.While value R² or determinat coefficient 87,9 % , the research of this study indicate to decision of candidate of studies choose economy fakulty University of Pekalongan can be explained by alls factor is 87,9 %. Key words : Strategic location, Affordable costs,Infrastructure, Interesting building,Lectures qualification, unaffected friends.